Left Atrial Myxoma and Antiphospholipid Syndrome—A Case Report - Meter, Mijo; Meter, Diana; Ceprnja, Toni; Perkovic, Dijana (International Journal of Angiology, 2021)
Cardiac myxoma (CM) is the most frequent type of primary cardiac neoplasm and is responsible for 58 to 80% of primary cardiac tumors. The antiphospholipid syndrome (APS) occurs most commonly in the systemic lupus erythematosus but it can be also found in other conditions. The coexistence of CM and APS is rarely described in the literature. We report an unusual case of the left atrial myxoma and concomitant APS in a female patient who presented with right-sided hemiplegia. Although rare, we must think about the CM in patients with a newly diagnosed APS and left atrial mass. Nevertheless, we must make a distinction from other possible cardiac structures, especially atrial thrombus. Transthoracic echocardiography is the most frequently used initial imaging modality to detect CM. The aim of this case report was to emphasize that additional imaging modalities and multidisciplinary approach are mandatory in making a proper diagnosis and to choose a further treatment strategy.
Keywords: cardiac tumor; antiphospholipid syndrome; echocardiography; left atrial myxoma; thromboembolism; ischemia